Kinesiotape Versus Home-Based Exercise for Reducing Pain and Disability in Elderly Osteoarthritis - Saraswati, Putu Ayu Sita; Nugraha, Made Hendra Satria (Jurnal Keterapian Fisik, 2025)
Background: Osteoarthritis (OA) in the knee causes various health problems, including pain and limited movement that reduces productivity and quality of life, causing disability. This study aims to determine the comparative effectiveness between home-based exercise and kinesiotape in lowering pain and disability in the elderly with knee osteoarthritis. Methods: It was an experimental study with a randomized pre-test and post-test control group design. There were 30 participants divided into 2 groups: Group 1 with Kinesiotape and Group 2 with Home-Based Exercise. The intervention was given 3 times per week for 4 weeks. Disability was measured by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and pain was measured by the Visual Analogue Scale (VAS). Results: The p-value for WOMAC and VAS scores before and after intervention is <0.001 in kinesiotape and Home-Based exercise interventions, which states that there is a significant improvement in lowering disability. Comparative analysis between groups also showed p< 0.001. Conclusion: Kinesiotape and home-based exercises are both effective in reducing knee pain and disability in elderly with knee OA. However, home-based exercises have proven to be more effective than kinesiotape. Home-based exercises are recommended as the primary intervention to decrease pain and disability in elderly individuals with genetic knee OA.